Multidimensional inequality and divergence: The Eurozone crisis in retrospect - Philipp Poppitz (University of Oldenburg, Department of Economics, 2019)
Variation in living standards across Europe, especially in income, has decreased over the last few decades, but the last recession brought convergence to a halt. This paper asks, first, whether sigma-convergence is found when other dimensions of inequality are taken into account, and second, whether the recent economic recovery led to renewed convergence. To assess sigma-convergence, I estimate transnational inequality in the euro area (EA-13) using a decomposable multidimensional inequality measure including income, occupational prestige, education, and employment status as key dimensions economic wellbeing and inequality. I quantify the contribution of factor shares to within- and between-group inequality across the euro area using a counterfactual decomposition method together with bootstrapped confidence intervals. The results show that, like income, multidimensional inequality increased significantly starting in 2008, mainly driven by income and employment status. Just two years later, in 2010, sigma-convergence started to decline, and in 2014 reached a level of divergence that had only been seen previously before the introduction of the euro. The income dimension best explains between-country divergence, but differences in employment status and the correlation between dimensions contributed substantially to within-country inequality. A formal club convergence test shows two of the European country clubs - Central Europe and Southern Europe - to be key drivers of divergence, with the exception of Spain as a potential outlier. The results show that the recent economic recovery in the euro area has brought about initial relief in multidimensional inequality, but that the level of transnational and between-country inequality as well as divergence remains high.
Keywords: D3; F15; I30; 330; multidimensional inequality; convergence; euro area; transnationalization; composite index